A systematic literature review on knowledge mapping for project risk management in the construction industry - Ullah, Safi; Deng, Xiaopeng; Amaechi, Chiemela Victor; Anbar, Diana R.; Ashraf, Muhammad Waqas (Frontiers in Built Environment, 2026)
IntroductionDue to the vastness of various construction practices globally, there is a need for knowledge mapping. Through the utilisation of research on Project Risk Management (PRM) for the Construction Industry, it is possible to carry out an investigation into the processes that pertain to knowledge management. To elaborate on the current research emphasis from three different points of view, namely the influence of political risk, risk assessment, and risk management strategies, the knowledge map analysis method has been elected as the appropriate approach. Knowledge mapping provides a systematic way to visualise research trends, identify gaps, and strengthen the understanding of PRM in international construction projects.MethodsThis scientific investigation, conducted in the field of risk management research, considers publications related to risk management. The study was conducted as a systematic literature review that adopted bibliometrics approach to explore the data from Dimensions database that have been reviewed using PRISMA 2020 statement. This study intends to present Knowledge Mapping for PRM in the Construction Industry, using data from 2000-2025. The analysis focused on three dominant research dimensions: political risk, risk assessment, and risk management strategies. It uses literature on studies that have been carried out on project risk and provides a comprehensive perspective on the topic.ResultsThe knowledge maps revealed distinct clusters of research activity across the three focal areas. Political risk emerged as a consistent theme in studies addressing international and cross-border construction contexts. Research on risk assessment showed significant methodological diversity, while studies on risk management strategies tended to emphasise both technological tools and organisational processes. Overall, the mapping highlighted increasing scholarly attention to integrated and holistic approaches to PRM. Some under-researched areas, particularly knowledge-transfer processes and cross-national learning mechanisms, were also identified. The findings demonstrate that knowledge mapping is a valuable tool for understanding the evolution and priorities of PRM research in the construction industry.DiscussionThe study makes use of Knowledge Mapping to offer some suggestions for research areas concerning risk management in international construction projects. These knowledge maps are founded on the investigations that were conducted on project risk management. However, the development of Knowledge Maps offers good contribution to knowledge for best practices in the construction sector. By identifying patterns and gaps, the study provides guidance for future investigations and encourages the development of improved risk management practices in global construction projects. The resulting knowledge maps contribute meaningfully to the field by supporting better decision-making, improving risk-handling capabilities, and informing best practices for the construction sector.